Molecular dissection of Janus kinases as drug targets for inflammatory diseases - Kwon, Sunghark (Frontiers in Immunology, 2022)
The Janus kinase (JAK) family enzymes are non-receptor tyrosine kinases that phosphorylate cytokine receptors and signal transducer and activator of transcription (STAT) proteins in the JAK-STAT signaling pathway. Considering that JAK-STAT signal transduction is initiated by the binding of ligands, such as cytokines to their receptors, dysfunctional JAKs in the JAK-STAT pathway can lead to severe immune system-related diseases, including autoimmune disorders. Therefore, JAKs are attractive drug targets to develop therapies that block abnormal JAK-STAT signaling. To date, various JAK inhibitors have been developed to block cytokine-triggered signaling pathways. However, kinase inhibitors have intrinsic limitations to drug selectivity. Moreover, resistance to the developed JAK inhibitors constitutes a recently emerging issue owing to the occurrence of drug-resistant mutations. In this review, we discuss the role of JAKs in the JAK-STAT signaling pathway and analyze the structures of JAKs, along with their conformational changes for catalysis. In addition, the entire structure of the murine JAK1 elucidated recently provides information on an interaction mode for dimerization. Based on updated structural information on JAKs, we also discuss strategies for disrupting the dimerization of JAKs to develop novel JAK inhibitors.